2015
DOI: 10.1136/vetreccr-2014-000162
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic removal of a large abdominal foreign body granuloma using single incision laparoscopic surgery (SILS) and extraction bag in a cheetah (Acinonyx jubatus)

Abstract: This case presents a thorn‐induced abdominal foreign body granuloma that was removed with single incision laparoscopic surgery and an extraction bag. An 11‐year‐old female cheetah presented for routine laparoscopic ovariectomy. Abdominal palpation detected a mid‐abdominal mass. Differential diagnoses were neoplasia and foreign body. Laparoscopic exploration of the peritoneal cavity revealed an omentalised mass, which was successfully removed with the aid of bipolar electrocoagulation. Microscopic investigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…One cheetah at site A had a concomitant intra-abdominal granuloma with associated abdominal effusion secondary to an abdominally-located thorn. This granuloma was removed laparoscopically [23].…”
Section: Animalsmentioning
confidence: 99%
“…One cheetah at site A had a concomitant intra-abdominal granuloma with associated abdominal effusion secondary to an abdominally-located thorn. This granuloma was removed laparoscopically [23].…”
Section: Animalsmentioning
confidence: 99%
“…The diagnosis in this case was arrived at using history and plain radiography following findings suspicions from palpation. Exploratory laparotomy was used for definitive diagnosis and subsequent removal of foreign bodies was previously used by others (Hartman et al, 2015;Papazoglou et al, 2010). Endoscopy has been used for removal of foreign bodies by previous workers (Hoefer and Levitan, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It is normal for ingested foreign bodies to perforate the wall of the gastrointestinal tract and end up causing granulomatous lesions in the abdomen (Hoefer and Levitan, 2013;Papazoglou et al, 2010). Hartman et al (2015) have recently reported a thorn induced pyogranulomatous lesion in the abdomen of a cheetah. It has been shown by previous workers that pollution of the environment with items such as litter, plastics and old toys has been associated with increased ingestion of these indigestible materials by livestock (Mushonga et al, 2015), pets (Boag et al, 2005;Hayes, 2009;Hobday et al, 2014;Papazoglou et al, 2010;Tyrrell and Beck, 2006) birds (Hoefer and Levitan, 2013) and even marine animals (De Majo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Other laparoscopic sterilization techniques have been reported including ovariohysterectomy, uterine horn occlusion, and laparoscopic‐assisted ovariohysterectomy . Laparoscopic ovariectomy has been performed in domestic cats using laser and bipolar electrocoagulation, and in 1 cheetah after removal of an abdominal foreign body . Laparoscopic ovariectomy, salpingectomy, ovariohysterectomy, and hysterectomy using multiple ports have been reported in the lion, and ovariectomy using single‐incision laparoscopic surgery (SILS) has been performed in 2 tigers .…”
mentioning
confidence: 99%
“…9- 13 Laparoscopic ovariectomy has been performed in domestic cats using laser and bipolar electrocoagulation, 14 and in 1 cheetah after removal of an abdominal foreign body. 15 Laparoscopic ovariectomy, salpingectomy, ovariohysterectomy, and hysterectomy using multiple ports have been reported in the lion, [16][17][18] and ovariectomy using single-incision laparoscopic surgery (SILS) has been performed in 2 tigers. 19 Laparoscopic sterilization of the cheetah has not been reported.…”
mentioning
confidence: 99%